MEDICINAL PROPERTIES OF ALHAGI PLANT - Khaydarov D.B (Modern American Journals, 2025)
Nature has always been a vital source for maintaining and restoring human health. Since ancient times, various plants have been used as therapeutic agents. Among these, the Alhagi species stands out, especially prevalent in arid regions such as Central Asia. This plant has long been valued as a natural remedy for different ailments.